2012
DOI: 10.1161/circep.112.971317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bipolar Electrode Spacing on Phrenic Nerve Stimulation and Left Ventricular Pacing Thresholds

Abstract: Background-Phrenic nerve stimulation (PNS) is a common complication of cardiac resynchronization therapy when left ventricular (LV) pacing occurs via a coronary vein. The purpose of this study was to evaluate the effects of bipolar electrode spacing on PNS and LV pacing thresholds. Methods and Results-Electrophysiology catheters with standard (2 mm-5 mm-2 mm) or modified (1 mm-5 mm-1 mm) interelectrode spacing was, respectively, inserted in a posterior/lateral cardiac vein in a randomized order in 6 anesthetiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The longest MID was observed during the LV-tip to RV-coil unipolar pacing configuration, indicating that this pacing configuration resulted in a wider electrical field. Most PN threshold were above 10 V if the distance between the LV lead and PN was over 20 mm, which was consistent with the study by Biffi et al [14]. Biffi et al also showed that the PN threshold rapidly increased when the cathode moved away from the PN, reaching a PN threshold of 10 V at a 0.5 ms PW with a distance of 20 mm.…”
Section: Discussionsupporting
confidence: 88%
“…The longest MID was observed during the LV-tip to RV-coil unipolar pacing configuration, indicating that this pacing configuration resulted in a wider electrical field. Most PN threshold were above 10 V if the distance between the LV lead and PN was over 20 mm, which was consistent with the study by Biffi et al [14]. Biffi et al also showed that the PN threshold rapidly increased when the cathode moved away from the PN, reaching a PN threshold of 10 V at a 0.5 ms PW with a distance of 20 mm.…”
Section: Discussionsupporting
confidence: 88%
“…10 On the other hand, current spread to adjacent structures may precipitate side effects.28 Smaller electrode spacing may increase the threshold for unwanted side effects without compromising the desired response. 29 Development of multichannel electrodes may further improve stimulation selectivity. 30 Finally, engagement of carotid chemoreceptors, which are known to regulate sympathetic activity and BP, 31 could differ between electrode designs.…”
Section: Discussionmentioning
confidence: 99%
“…The narrowspaced electrodes, "short bipolar," were designed to reduce the chance of stimulation of the phrenic nerve without compromising pacing capture thresholds (PCTs). 21 The VectorExpress feature of the accompanying pulse generator allows for automatic and rapid testing of the PCT and impedance for all possible vectors. This is usually accomplished in less than 3 minutes.…”
Section: Device Descriptionmentioning
confidence: 99%